Whole-genome sequence of a high-temperature edible mushroom Pleurotus giganteus (zhudugu) - Yu, Hailong; Zhang, Meiyan; Sun, Yating; Li, Qiaozhen; Liu, Jianyu; Song, Chunyan; Shang, Xiaodong; Tan, Qi; Zhang, Lujun; Yu, Hao (Frontiers in Microbiology, 2022)
Most of the sequenced wood-rotting edible mushroom produce fruiting body at relative low temperature. Little information has been known about the high temperature wood-rotting mushroom. Here, we performed de novo sequencing and assembly of the genome of a high temperature edible mushroom P. giganteus from a monokaryotic strain zhugudu2 using the Illumina and Pac-Bio CLR sequencing technologies. Pleurotus giganteus, also known as Zhudugu in China, is a well-known culinary edible mushroom that has been widely distributed and cultivated in China, Southeast Asia, and South Asia. The genome consists of 40.00 Mb in 27 contigs with a contig N50 of 4.384 Mb. Phylogenetic analysis reveals that P. giganteus and other strains in Pleurotus clustered in one clade. Phylogenetic analysis and average nucleotide identity analysis indicated that the P. giganteus genome showed a closer relationship with other Pleurotus species. Chromosome collinearity analysis revealed a high level of collinearity between P. ostreatus and P. giganteus. There are 12,628 protein-coding genes annotated in this monoploid genome. A total of 481 enzymes accounting for 514 CAZymes terms were identified in the P. giganteus genome, including 15 laccases and 10 class II peroxidases predicted in the genome, which revealed the robustness of lignocellulose degradation capacity of P. giganteus. The mating-A type locus of P. giganteus consisted of a pair of homeodomain mating-type genes HD1 and HD2. The mating-B type locus of P. giganteus consisted of at least 4 pheromone receptor genes and 3 pheromone genes. The genome is not only beneficial for the genome-assisted breeding of this mushroom but also help us to understand the high temperature tolerance of the edible mushroom.